Transient Stability Analysis of the IEEE 14-Bus Test System Using Dynamic Computation for Power Systems (DCPS) - Hashim, N.; Hamzah, N.; Latip, M.F. Abdul; Sallehhudin, A.A. (2012 Third International Conference on Intelligent Systems Modelling and Simulation, 2012)
Transient Stability Analysis (TSA) is a major analysis in the operation of power systems, due to the increasing stress on power system networks. One of the main goals of this analysis is to gather critical information, such as critical clearing time (tCCT) of the circuit breakers for faults in the system. tCCT is defined as the maximum time between the fault initiation and its clearing, such that the power system is transiently stable. This paper presents a transient stability analysis of the IEEE 14 bus test system using Dynamic Computation for Power Systems (DCPS) software package. This C++ based software package has the ability to handle systems up to 1000 buses and 250 generators, providing an alternative to expensive commercial software packages. To analyze the effect of the distance of the fault location and critical clearing time on the system stability, a three-phase fault has been applied at five different locations in the system. The stability of the system has been observed based on the simulation graphs of terminal voltage, machine's rotor angle, machine's speed and output electrical power. The simulation results showed that tCCT decreases as the fault location becomes closer to the main generator.